1982
DOI: 10.3181/00379727-170-41465
|View full text |Cite
|
Sign up to set email alerts
|

Partial Chemical Characterization of a Natriuretic Substance in Rat Atrial Heart Tissue

Abstract: Extracts of atrial and ventricular rat heart tissue were prepared in phosphatebuffered saline and boiled (PBS-boiled) or in acetic acid and fractionated using Sephadex G-75. The extracts were injected intravenously into anesthetized nondiuretic (i.e., not hydrated) rats to assay for natriuretic activity. PBS-boiled atrial extract caused urinary sodium excretion (UNaV) to increase significantly (P < 0.05) by 672 5 307% (+SE) during the 10 min after injection; whereas no significant change in U,,V occurred after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
34
2
1

Year Published

1984
1984
2009
2009

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(38 citation statements)
references
References 4 publications
1
34
2
1
Order By: Relevance
“…Recently, a number of peptides with potent natriuretic, diuretic (1)(2)(3)(4)(5)(6)(7), and vasorelaxant activities (8)(9)(10) have been isolated from mammalian atria. Mammalian atrial cardiocytes contain specific granules which morphologically resemble those found in peptidesecreting cells (I 1).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a number of peptides with potent natriuretic, diuretic (1)(2)(3)(4)(5)(6)(7), and vasorelaxant activities (8)(9)(10) have been isolated from mammalian atria. Mammalian atrial cardiocytes contain specific granules which morphologically resemble those found in peptidesecreting cells (I 1).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, efforts have been devoted to the purification and chemical characterization of ANF in the atrial muscle of the rat and other mammals (4)(5)(6)(7). However, these studies have been hampered by the scarcity of material available from rat atrial homogenates and also by the apparent heterogeneity of the biologically active factor (4,(7)(8)(9).…”
mentioning
confidence: 99%
“…NatL Acad ScL USA 81 (1984) erated by trypsin treatment of the high molecular weight fraction correspond to the low molecular weight peptides obtained during our extraction procedure. One possibility is that the peptide(s) may exist in the atrial granules in the high molecular weight form and that our efforts (7) and those of others (4)(5)(6) to extract the peptides either with heat or acid (4-7) result in the proteolytic cleavage that induce the formation of the smaller peptide fraction. The high molecular weight peptide(s) may be either the post-translational precursor form(s) of the active peptide (e.g., prohormone) or the secreted form of the peptide, which is processed and activated at some other site(s).…”
Section: Discussionmentioning
confidence: 99%
“…The contents and function of granules located in mammalian cardiac atria remain to be established. A possible homeostatic function is implied by the demonstration that atrial stretch or myocardial volume overload cause a natriuresis and diuresis (3) and that atrial (but not ventricular) extracts possess natriuretic and diuretic activity when administered to rats (4)(5)(6). Partial purification of the atrial extract indicates the presence of several fractions with natriuretic activity (5,6).…”
mentioning
confidence: 99%